Current Practice in Occupational Therapy for COVID-19 and Post-COVID-19 Conditions - C. von Zweck; D. Naidoo; P. Govender; R. Ledgerd (Occupational Therapy International)
The onset of the pandemic highlighted the need for a review of rehabilitation practices to ensure coordinated, effective, and efficient services for people affected by COVID-19. This paper reports on a global survey highlighting the delivery of occupational therapy services to people with COVID-19/post-COVID-19 condition (PCC) and makes recommendations to facilitate quality service delivery for this population. An online cross-sectional descriptive survey was developed and distributed to the global occupational therapy community via member organisations and communication channels of the World Federation of Occupational Therapists to collect information for this study. The survey obtained qualitative and quantitative data from respondents who were occupational therapists or occupational therapy assistants regarding (i) demographic characteristics, (ii) work experience with persons with COVID-19 and PCC, (iii) modes of working, (iv) education and training, (iv) occupational therapy intervention provided to persons with COVID-19 and PCC, and (v) the perceived quality of the occupational therapy services provided. Findings indicate that respondents provided a range of occupational therapy interventions for people affected by COVID-19/PCC aligned with evidence-based practice guidelines. While respondents identified a strong role for occupational therapy and generally rated their services as effective, issues related to the accessibility of their services impacted quality and user satisfaction. The study highlighted the need to advocate for access to occupational therapy to facilitate engagement in desired and needed occupations for COVID-19 survivors. Other recommendations emerging from the findings include the need to develop, disseminate, and use research evidence for guiding services for people with COVID-19/PCC, create quality service standards, and ensure the availability of necessary resources and supports such as referral pathways and screening criteria, availability of staff, training, personal protective equipment, and assistive devices and technology.